First records of the spider wasps Ctenocerus Dahlbom and Paraclavelia Haupt from Asia, with discussions on the systematics of Ctenocerinae (Hymenoptera: Pompilidae) - Shimizu, Akira; Broad, Gavin; Yoshimura, Jin; Pitts, James P. (European Journal of Taxonomy, 2022)
We describe two new species of Ctenocerinae (Pompilidae) from Asia, i.e., Ctenocerus srilankae Shimizu sp. nov. from Sri Lanka and Paraclavelia arabiae Shimizu sp. nov. from Oman. These represent the first records of Ctenocerus Dahlbom, 1845 and Paraclavelia Haupt, 1930 in Asia. Two new combinations and a new synonymy are proposed: Ctenocerus fasciatus (Smith, 1851) (= Micropteryx fasciata Smith, 1851); Paraclavelia decipiens (Arnold, 1932) (= Clavelia decipiens Arnold, 1932); and Ctenocerus Dahlbom, 1845 (= Euclavelia Arnold, 1932). We discuss the difficulty of systematics of Ctenocerinae at generic level. The head and pronotal structures of Ctenocerus and Paraclavelia are presumably specialized for preying on trapdoor spiders. These structures are considered to have evolved independently of other unrelated parasitoid Pompilidae that have been confirmed or proposed to prey on trapdoor spiders. We also discuss the biogeographical distribution of these genera.